Phono-syntactic error pattern analysis in impromptu speaking among English learners: a content analysis - Angelie V. Temario; Harold John U. Mamites; April Jane G. Sales; Marcelina S. Deiparine (International Journal of Evaluation and Research in Education (IJERE), 2026)
Second language learners, particularly Filipino learners of English, often experience linguistic difficulties in producing accurate phonological and syntactic forms, especially during spontaneous speaking tasks. This study examines the dominant phono-syntactic error patterns found in impromptu speaking performances and explores their pedagogical implications using Corder’s error analysis framework. Employing a qualitative descriptive research design, the study analyzed recorded impromptu speaking performances of 36 Bachelor of Arts in English Language (BAEL) students. The analysis revealed that in the phonological aspect, segmental errors were more prevalent than suprasegmental errors, with vowel substitution emerging as the most frequent error type, accounting for 22 errors (57.1%). In the syntactic aspect, misformation was identified as the most dominant error category, with 164 errors (54.88%). These findings suggest that while learners demonstrate emerging grammatical awareness, they still encounter difficulties in maintaining phonological and syntactic accuracy during spontaneous speech production. The study highlights the importance of integrating pronunciation and grammar instruction within communicative speaking activities. Furthermore, impromptu speaking tasks serve as an effective diagnostic tool for identifying learners’ linguistic challenges and guiding instructional strategies aimed at improving spoken language proficiency.